P17.12.B HOXD13 gene plays a role as a putative master epigenetic regulator in glioma recurrence and progression. (5th September 2022) - Morosini, N S; Sabedot, T S; Cazacu, S L; deCarvalho, A; Noushmehr, H
Abstract: Background: Adult diffuse glioma is a heterogenous brain tumor group that has malignant potential and recurring properties. Glioma CpG island methylator phenotype (G-CIMP) associated with chromatin remodeling encompasses two different methylation degrees: G-CIMP-high and G-CIMP-low that have high levels of DNA methylation and loss of DNA methylation, respectively. G-CIMP-high confers a more favorable prognosis and better predictive values by altering transcriptional dynamics and inhibiting the gene expression. However, some IDH-mutant G-CIMP-high undergo a demethylation process progressing to G-CIMP-low leading to tumor recurrence and aggressiveness. Material and Methods: We have performed Chromatin Immunoprecipitation Sequencing (ChIP-Seq) on DNA extracted from nine (9) fresh frozen primary tumor tissues belonging to G-CIMP-high group and four (4) belonging to G-CIMP-low group. We have processed the sequencing data by using FastQC (v.:0.11.5), bwa-mem (v.:0.7.15) and picard tool (v.:2.7.1). The ChIP-seq peaks and the differentially bound peaks were obtained using MACS2 (v.:2.1.1) and DiffBind (v.:3.4.11), respectively. We have integrated transcriptomic, epigenomic and genomic data to investigate the impact of H3K4me3 and H3K27ac in the epigenome of G-CIMP-low and high tumors. Results: Initial results showed that the differentially bound H3K27ac and H3K4me3 peak gains and losses are located mainly in intronic and intergenic regions. The integration between epigenetic and transcriptomic data revealed that the promoter of the HOXD13 gene upregulated in GCIMP-low presents an active regulatory region and is enriched by H3K27ac and H3K4me3 sites. We were able to identify that GCIMP-low, in addition to presenting more downregulated genes than GCIMP-high, also has greater affinity to the H3K27ac peaks. In GCIMP-low, we identified 312 promoter regions significantly enriched by the epigenetic biomarker H3K27ac and 67 promoters with loss of affinity for H3K27ac, with the regions enriched by H3K27ac highly associated with the presence H3K4me3 marks. Functional genomic analysis targeting HOXD13 by using CRISPR in a representative glioma cell line shows that HOXD13 is critical for impairing the proliferative state that drives glioma progression.Conclusion: We mapped the enrichment of histone modifications in the TSS of differentially expressed genes in G-CIMP-high and G-CIMP-low identifying both the susceptibility of GIMP-low to interact with H3K27ac and the fact that the progression of GCIMP-high to G-CIMP-low can be explained by the association between H3K27ac gain and the inhibition of gene expression. Also, we predicted the HOXD13 gene as a putative master epigenetic regulator of the G-CIMP demethylation process and, consequently, of tumor recurrence and progression, over time.